Differential effects of the hydrophobic surfactant proteins on the formation of inverse bicontinuous cubic phases - Chavarha, Mariya (Langmuir : the ACS journal of surfaces and colloids, 2012)
Prior studies have shown that the biological mixture of the two hydrophobic surfactant proteins, SP-B and SP-C, produces faster adsorption of the surfactant lipids to an air/water interface, and that they induce 1-palmitoyl-2-oleoyl phosphatidylethanolamine (POPE) to form inverse bicontinuous cubic phases. Previous studies have shown that SP-B has a much greater effect than SP-C on adsorption. If the two proteins induce faster adsorption and formation of the bicontinuous structures by similar mechanisms, then they should also have different abilities to form the cubic phases. To test this hypothesis, we measured small-angle X-ray scattering on the individual proteins combined with POPE. SP-B replicated the dose-related ability of the combined proteins to induce the cubic phases at temperatures more than 25 °C below the point at which POPE alone forms the curved inverse-hexagonal phase. With SP-C, diffraction from cubic structures was either absent or present at very low intensities only with larger amounts of protein. The correlation between the structural effects of inducing curved structures and the functional effects on the rate of adsorption fits with the model in which SP-B promotes adsorption by facilitating formation of an inversely curved, rate-limiting structure